Akt isoform specificity drives intrinsic immune regulation during HSV-1 infection - Rahul K. Suryawanshi; Chandrashekhar D. Patil; Hemant Borase; Deepak Shukla (Proceedings of the National Academy of Sciences, 2025)
Akt isoforms are generally considered functionally redundant, contributing to total Akt activity. However, during HSV-1 infection, Akt1 and Akt2 knockout animals exhibited distinct antiviral responses. Unexpectedly, in the absence of Akt1, Akt2 played a unique role in regulating cytokine production and inactivating proapoptotic transcription factor FoxO3a, a mechanism not shared by Akt1. These findings provide the clearest in vivo evidence yet that Akt isoforms are not functionally redundant, revealing distinct immune-regulatory roles for each isoform and suggesting a broader principle for fine-tuning immunity and cell death across diverse pathological settings.